Prevalence of neuromyths among students and pre-service teachers - Marina V. Khramova; Tatyana V. Bukina; Nikita M. Smirnov; Semen A. Kurkin; Alexander E. Hramov (Humanities & Social Sciences Communications, 2023)
Abstract Recent studies have shown that the knowledge of society about the functioning of the brain does not correspond to neuroscience data. The high prevalence of neuromyths can become a problem in the development of educational technologies. The goal of this study is to identify the prevalence of neuromyths among pre-service teachers and students of other faculties. The prevalence of neuromyths among 958 university students was studied using an anonymous survey. It was found that the specialty influenced the results: chemistry and biology students, as well as physics, mathematics, and computer science students, answered better. The effect of education is weak. Nevertheless, it has led to an alignment of results between the specialties in the older group. Self-education has a significant positive effect on students’ recognition of neurofacts. The study confirms that certain neuromyths are especially popular among students and allows us to draw conclusions about the prevalence of neuromyths among future teachers.